Employer organisations transformed. (18th December 2018) - Demougin, Philippe; Gooberman, Leon; Hauptmeier, Marco; Heery, Edmund
Abstract: Employer organisations and the literature examining them have transformed since their inception in the 19th century. We systematically review this literature and the evolving role of employer organisations by focusing on the most cited publications of this body of academic work. This article provides a synopsis of our current understanding of employer organisations, identifies gaps in our knowledge, and develops the following argument. Employer organisations adapted to changing socio‐economic contexts by evolving within and across three roles—as industrial relations actor, political actor, and service provider. Historically, employer organisations were predominantly understood as an industrial relations actor with collective bargaining as their defining activity. However, employer organisations also influenced the political process through lobbying and participating in corporatist arrangements, although more recently their provision of member services has grown in scope and importance.